To bite off more than one can Chew?: Parents' Opinion in Open and Distance Learning (ODL) among school children in Petaling Jaya / Nur Izza Nafisa Fairuz Nizzam, Siti Nur Kamalia Zainal and Nur Zafifa Kamarunzaman - Nizzam, Nur Izza Nafisa Fairuz; Zainal, Siti Nur Kamalia; Kamarunzaman, Nur Zafifa (2021)
The emergence of the Covid-19 pandemic is a risk health issue, and it has had an impact all over the world. In Malaysia, the rules of critical physical distancing and wearing a mask have been executed in each state (Times, 2020). The country's education system also had taken a precautionary measure in shutting all schools operations and replaced it with Online and Distance Learning (ODL) (Teräs, 2020). This pandemic strongly impacts education, where learning approaches are changed from physical classes to ODL. Universally, over 1.2 billion children had to continue learning from home. Consequently, the Covid-19 pandemic has changed the lifestyle and education with the idiosyncratic rise of e-learning and might negatively impact the children. Therefore, the researchers intended to investigate the parents' opinions on ODL concerning their children's health, time management, and skill requirements in Petaling Jaya, Selangor during the Covid-19 outbreak.